Citizen, cyber government and the legal aspects - Zulhuda, Sonny (2014)
The focus areas of cyber government in Malaysia can be found in several issues, e.g. modernizing the government machinery, an increasing reliance on the Internet, public acceptance, capacity building, issues of privacy and security and the open data and innovations. This presentation focuses more on the legal aspects of cyber government.